2012
DOI: 10.1017/s1041610211002493
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in Alzheimer's disease: different factors associated with complementary ratings by patients and family carers

Abstract: Mild to moderate community-dwelling AD patients and their carers (with different perspectives) agree within an acceptable range in QoL ratings but the ratings are driven by different factors, and consequently are not interchangeable but complementary. They provide valuable information when used separately, not in a composite score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
121
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(144 citation statements)
references
References 56 publications
(123 reference statements)
16
121
2
3
Order By: Relevance
“…No clear or consistent associations between QOL and socio-demographic variables including age, education and gender were found (Banerjee et al, 2009). A consistent pattern is found in the literature for lower QOL and high levels of depressive symptoms (Bosboom, Alfonso, Eaton & Almeida, 2012;Logsdon, Gibbons, McCurry, & Teri, 2002) and more dependence in activities of daily living (Black et al, 2012;Conde-Sala, GarreÀOlmo, Turr oÀGarriga, L opezÀPousa, & VilaltaÀFranch, 2009). In general, high levels of behavioral problems are associated with decreased QOL (Banerjee et al, 2009).…”
Section: Difficulties In These Areasmentioning
confidence: 75%
“…No clear or consistent associations between QOL and socio-demographic variables including age, education and gender were found (Banerjee et al, 2009). A consistent pattern is found in the literature for lower QOL and high levels of depressive symptoms (Bosboom, Alfonso, Eaton & Almeida, 2012;Logsdon, Gibbons, McCurry, & Teri, 2002) and more dependence in activities of daily living (Black et al, 2012;Conde-Sala, GarreÀOlmo, Turr oÀGarriga, L opezÀPousa, & VilaltaÀFranch, 2009). In general, high levels of behavioral problems are associated with decreased QOL (Banerjee et al, 2009).…”
Section: Difficulties In These Areasmentioning
confidence: 75%
“…The severity of depressive symptoms has shown a strong reverse association both with self-assessed and for proxy-rated QoL in all stages of dementia [Barca et al 2011;Bosboom et al 2012;Hoe et al 2006;Hoe et al 2007;Karttunen et al 2011], although the observation is less consistent in more severe cases [Banerjee et al 2009].…”
Section: Clinical Determinants Of Quality Of Life In Dementiamentioning
confidence: 98%
“…Of note, none of the studies had adopted assessment instruments which are validated in patients with AD; therefore, no clear conclusion can be drawn from them [Takeda et al 2006]. Conversely, some observational studies have reported an independent association between patient-rated QoL, measured with appropriate instruments, and treatment with antidementia agents [Bosboom et al 2012], especially CIs [Hoe et al 2007].…”
Section: Direct Assessmentmentioning
confidence: 99%
“…2 There is evidence that people with mild to moderate dementia can reliably rate their own QoL. 3 However, there is substantive literature on the differences between selfreported and caregiver-reported QoL in people with dementia (PwD). [4][5][6] These differences have been interpreted as indicative of low level of agreement, 7 disagreement, 8 moderately low correlation, 9 and even high correlation.…”
Section: Introductionmentioning
confidence: 99%